New findings of kinase switching in gastrointestinal stromal tumor under imatinib using phosphoproteomic analysis. Issue 11 (14th June 2013) - Takahashi, Tsuyoshi; Serada, Satoshi; Ako, Maiko; Fujimoto, Minoru; Miyazaki, Yasuaki; Nakatsuka, Rie; Ikezoe, Takayuki; Yokoyama, Akihito; Taguchi, Takahiro; Shimada, Kazuki; Kurokawa, Yukinori; Yamasaki, Makoto; et al.
<x xml:space="preserve">Abstract</x> Despite the revolutionary effects of imatinib on advanced gastrointestinal stromal tumors (GISTs), most patients eventually develop disease progression following primary resistance or acquired resistance driven by secondary‐resistant mutations. Even in radiographically vanishing lesions, pathology has revealed persistent viable cells during imatinib therapy, which could lead to the emergence of drug‐resistant clones. To uncover the mechanisms underlying these clinical issues, here we examined imatinib‐induced phosphoproteomic alterations in GIST‐T1 cells, using our quantitative tyrosine phosphoproteomic analysis method, which combined immunoaffinity enrichment of phosphotyrosine‐containing peptides with isobaric tags for relative and absolute quantitation (iTRAQ) technology. Using this approach, we identified 171 tyrosine phosphorylation sites spanning 134 proteins, with 11 proteins exhibiting greater than 1.5‐fold increases in tyrosine phosphorylation. Among them, we evaluated FYN and focal adhesion kinase (FAK), both of which are reportedly involved in proliferation and malignant alteration of tumors. We confirmed increased tyrosine phosphorylation of both kinases by western blotting. Inhibition of FYN and FAK phosphorylation each increased tumor cell sensitivity to imatinib. Furthermore, a FAK‐selective inhibitor (TAG372) induced apoptosis of imatinib‐resistant GIST‐T1 cells and decreased the imatinib IC50. These results indicate that FYN or FAK might be potential therapeutic targets to overcome resistance to imatinib in GISTs. Additionally, we showed that the iTRAQ‐based quantitative phosphotyrosine‐focused phosphoproteomic approach is a powerful method for screening phosphoproteins associated with drug resistance.